A randomised oral fluoride retention study comparing intra-oral kinetics of fluoride-containing dentifrices before and after dietary acid exposure. (November 2020) - Burnett, Gary; Nehme, Marc; Parkinson, Charles; Karwal, Ritu; Badrock, Thomas; Thomas, Gavin Vaughan; Hall, Peter
Highlights: Fluoride can protect enamel from demineralisation and promote remineralization. A sodium fluoride/potassium nitrate/cocamidopropyl betaine dentifrice was examined. Compared to a NaF/KNO3 /sodium lauryl sulphate/tetrasodium pyrophosphate dentifrice. Greater salivary fluoride/calcium ion concentration found with the test dentifrice. Formulation excipients may impact fluoride and calcium ion oral cavity retention. Abstract: Objective: This exploratory, randomised, single-blind, crossover, study evaluated fluoride and calcium ion concentrations and pH following use of one of two 1450 ppm fluoride (NaF), 5% w/w KNO3 dentifrices: (1) test dentifrice (with cocamidopropyl betaine) with an orange juice (OJ) rinse; (2) test dentifrice with a deionized (DI) water rinse or (3) comparator dentifrice (with sodium lauryl sulphate and tetrasodium pyrophosphate) with an OJ rinse. Design: Eighteen participants used their assigned dentifrice, rinsed with DI water, then expectorate was collected. Sixty min post-brushing, participants rinsed with OJ or DI water then expectorate was collected. Saliva samples were collected pre-brushing and at 1, 5, 10, 15, 30 and 60 min post-brushing and following the 60 min OJ/DI water rinse. The pH of samples was taken. Results: Significant differences (p < 0.05) were found in salivary fluoride ion concentrations between test and comparator dentifrices at 30 and 60 min and following the 60 min OJ rinse, favouring the former. Significant differences were also found between test and comparator dentifrices for salivary calcium ion concentration at 1, 5 and 10 min (p < 0.0001), favouring the former, and between test or comparator + OJ rinse and test + water rinse (p < 0.005), favouring the latter. No pH differences were shown prior to OJ/water rinse. Products were generally well-tolerated. Conclusions: Results confirmed that acid-labile fluoride is released from the oral cavity following a dietary acid challenge and showed that formulation excipients may impact on retention of such.